The Seasonality and Spatial Landscape of the Historical Climate-Based Suitability of Aedes-Borne Viruses in Four Atlantic Archipelagos - Martim A. Geraldes; Marta Giovanetti; Mónica V. Cunha; José Lourenço (Viruses)
While archipelagos have a demonstrated role in the stepping-stone process of the global dissemination of Aedes-borne viruses, they are often neglected in epidemiological and modelling studies. Over the past 20 years, some Atlantic archipelagos have witnessed a series of Aedes-borne viral outbreaks, prompting inquiries into the local historical suitability for transmission. In this study, the climate-based suitability for transmission of Aedes-borne viruses between 1980 and 2019 across Madeira, the Canaries, Cape Verde, and São Tomé e Príncipe archipelagos was estimated. For each island, we characterized the seasonality of climate-based suitability, mapped the spatial landscape of suitability, and quantified the historical effects of climate change. Results show that both island-level suitability and the historical impact of climate change decrease with distance from the equator, while significant seasonality patterns are observed only in subtropical climates. This study provides a unique historical perspective on the role of climate in shaping Aedes-borne virus transmission potential in Atlantic archipelagos. The findings herein described can inform local public health initiatives, including human-based prevention, targeted viral surveillance, and mosquito control programs.